IMPLEMENTASI PERDA KABUPATEN INDRAGIRI HILIR NO 5 TAHUN 2016 TENTANG KAWASAN TANPA ROKOK - jurnalmap map; Masnaria ÔÇÄÔÇÄÔÇÄ; Sri Mulyani (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This study aims to describe the implementation of Indragiri Hilir District Regulation No. 5 of 2016 concerning No-Smoking Areas. This type of research is descriptive with qualitative methods. Research data obtained from interviews, observations and documentation. Data analysis uses interactive data analysis from Miles and Huberman. Based on the results of the study, researchers obtained information that the application of the No Smoking Area in the Indragiri Hilir District Health Office has been going well, but several obstacles were still found, namely from the socialization, resources, disposition and bureaucratic structure. The implementation of the No Smoking Area policy in several other government offices is still not going well, there are still many cigarette butts and cigarette ashtrays found in government offices. The lack of compliance is due to the absence of strict sanctions and the absence of committees or oversight teams for the implementation of the No Smoking Area policy. Keywords: policy, implementation, no-smoking area